Identifying Successful HF Strategies for Investing in Emerging Markets - D. V., Mahesh (Indian Journal of Finance, 2009)
The inevitable has finally happened. The sub-prime crisis that has resulted from the real estate bust in the US has destroyed investor wealth worth trillions of dollars across the world. The burst has claimed high profile investment banks like Bear Sterns, Lehman Brothers, AIG, one of the most venerable insurers in the world. The US government is planning to make provisions for an $700 billion bailout package that would buy all the bad loans and related products sold by US commercial and investment banks.A downshift of US consumption growth will affect Asia unevenly. Rapidly growing emerging economies like India and China have ample cushion to withstand such a blow, whereas Asian countries like Japan, South Korea may see the downturn. Thus hedge fund managers are lining up to hedge their investments in emerging markets. But emerging markets are in incubation stage with lack of proper regulatory measures and research options. This report gives overview of hedge fund strategies in emerging economies.